Computer-assisted femur fracture reduction - Frank, Johannes; Gritzbach, Bernd; Winter, Christian; Maier, Bernd; Marzi, Ingo (European journal of trauma and emergency surgery, 2010)
When using intramedullary nailing of femur fractures false axis alignment or malrotation is the greatest deterrent to successful reduction often causing extended x-ray exposure and the need to revert to an open procedure. The aim of this study was to demonstrate the advantages of using a trauma navigation system during intramedullary nailing of femur fractures.